2021
DOI: 10.3390/w13202839
|View full text |Cite
|
Sign up to set email alerts
|

Digested Sludge Quality in Mesophilic, Thermophilic and Temperature-Phased Anaerobic Digestion Systems

Abstract: Anaerobic digestion (AD) technology is commonly used to treat sewage sludge from activated sludge systems, meanwhile alleviating the energy demand (and costs) for wastewater treatment. Most often, anaerobic digestion is run in single-stage systems under mesophilic conditions, as this temperature regime is considered to be more stable than the thermophilic one. However, it is known that thermophilic conditions are advantageous over mesophilic ones in terms of methane production and digestate hygienisation, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The results of the monodigestion at 25 • C, TSS, and DSS trials yielded maximum values of 130.39 mL CH 4 /g VS and 163.09 mL CH 4 /g VS at a retention time of 30 days, respectively. The methane yield obtained by DSS shows what Lanko et al [56] indicate: the digested sludge is the best to be used as fuel because it has organic matter that was not transformed into biogas in the previous anaerobic digestion. Due to the values obtained in digestion, it was decided to make a codigestion between thickened secondary sludge and digested secondary sludge at a temperature of 25 • C. Figure 2 shows the biochemical methane potential of monodigestion and codigestion at different temperatures.…”
Section: Digestivity Assays and Biochemical Methane Potentialsupporting
confidence: 54%
“…The results of the monodigestion at 25 • C, TSS, and DSS trials yielded maximum values of 130.39 mL CH 4 /g VS and 163.09 mL CH 4 /g VS at a retention time of 30 days, respectively. The methane yield obtained by DSS shows what Lanko et al [56] indicate: the digested sludge is the best to be used as fuel because it has organic matter that was not transformed into biogas in the previous anaerobic digestion. Due to the values obtained in digestion, it was decided to make a codigestion between thickened secondary sludge and digested secondary sludge at a temperature of 25 • C. Figure 2 shows the biochemical methane potential of monodigestion and codigestion at different temperatures.…”
Section: Digestivity Assays and Biochemical Methane Potentialsupporting
confidence: 54%
“…However, the most-discussed biomass for TAD is sewage sludge, whose digestate quality has been examined from the final disposal point of view. Lanko et al [13] reported the digestate quality of single-stage mesophilic (SMAD) and thermophilic AD (STAD) and double-stage thermophilic AD (DTAD) systems for treating waste-activated sludge, in terms of the dewaterability, pathogenic safety, and lower calorific value (LCV). The experimental results showed that the DTAD system is the most beneficial in terms of organic matter degradation efficiency (32.4% against 27.2% for STAD and 26.0% for SMAD), producing a digestate with high dewaterability (8.1-9.8% worse than for STAD and 6.2-12.0% better than for SMAD) and pathogenic safety (coliforms and Escherichia coli were not detected, and Clostridium perfringens were counted up to 4.8-4.9 × 10 3 CFU/g, when it was 1.4-2.5 × 10 3 CFU/g only for STAD, and 1.3-1.8 × 10 4 CFU/g for SMAD with the lowest LCV (19.2% against 15.4% and 15.8% under STAD and SMAD, respectively)).…”
Section: Impact Of Thermophilic Inoculum On Admentioning
confidence: 99%
“…Any deviation from the optimum temperature range denatures or inactivates the enzyme protein, which in turn lowers its activity. Among the various temperature ranges of AD, thermophilic anaerobic digestion (TAD), wherein the digester is operated at 50-60 • C [13] using microbial community functioning under thermophilic conditions, has gained interest over the common and convenient process, mesophilic anaerobic digestion (MAD) at 25-45 • C [14,15], due to the enhanced organic loading rate (OLR) and substrate degradation [16]. Higher degradation of the organic matter is due to the improved solubility of the substrates (composed of polysaccharides, proteins, lipids, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The optimum operating conditions for AD systems depend on the specific type of substrate used and the desired methane production rate. Lanko I. et al [26] have found that thermophilic conditions (55-60 • C) were more suitable for the digestion of energy crops and animal manure, while the digestion of food waste and sewage sludge had greater performance under mesophilic conditions (35-40 • C). The hydraulic retention time (HRT) and organic load rate (OLR) also played a role and were critical parameters affecting the methane concentration in biogas.…”
Section: Introductionmentioning
confidence: 99%